2016
DOI: 10.1038/emm.2015.102
|View full text |Cite
|
Sign up to set email alerts
|

Charged MVB protein 5 is involved in T-cell receptor signaling

Abstract: Charged multivesicular body protein 5 (CHMP5) has a key role in multivesicular body biogenesis and a critical role in the downregulation of signaling pathways through receptor degradation. However, the role of CHMP5 in T-cell receptor (TCR)–mediated signaling has not been previously investigated. In this study, we utilized a short hairpin RNA-based RNA interference approach to investigate the functional role of CHMP5. Upon TCR stimulation, CHMP5-knockdown (CHMP5KD) Jurkat T cells exhibited activation of TCR do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Additionally, CHMP5 prevents Bcl-2, a widely recognized apoptosis suppressor gene that intrinsically regulates apoptosis, from deleterious oxidation by reactive oxygen species (ROS) formation ( Adoro et al, 2017 ). Furthermore, it has been shown that CHMP5 has a key role in T-cell receptor signaling and its deficiency affects T-cell receptor expression on the cell surface ( Wi et al, 2016 ). However, the role of CHMP5 in IS has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CHMP5 prevents Bcl-2, a widely recognized apoptosis suppressor gene that intrinsically regulates apoptosis, from deleterious oxidation by reactive oxygen species (ROS) formation ( Adoro et al, 2017 ). Furthermore, it has been shown that CHMP5 has a key role in T-cell receptor signaling and its deficiency affects T-cell receptor expression on the cell surface ( Wi et al, 2016 ). However, the role of CHMP5 in IS has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…To generate control (Ctrl) THP-1 and AMPKα1KD THP-1 cells, lentivirus containing small hairpin RNA (shRNA) targeting human AMPKαl (Santa Cruz Biotechnology, sc-29673-V, Santa Cruz, CA, USA) and control shRNA lentivirus (Santa Cruz Biotechnology, Santa Cruz, sc-108080, Santa Cruz, CA, USA) were used to infect THP-1 cells. Ctrl THP-1 and AMPKα1KD THP-1 cells were selected as previously described [8,[23][24][25][26].…”
Section: Generation Of Ampkα1-knockdown (Ampkα1kd) Thp-1 Cellsmentioning
confidence: 99%
“…Western blotting and IP assays were performed as previously described [13,15,16,[23][24][25][26][27][28][29][30][31]. Briefly, mock vector as control vector, MYC-TRAF6, FLAG-AMPKαl, and MYC-BECN1 were transfected into HEK293T cells using Lipofectamine 2000 for 38-48 h. Cell lysates were immunoprecipitated with anti-FLAG or anti-MYC antibody.…”
Section: Western Blotting Analysis and Immunoprecipitation (Ip) Assaysmentioning
confidence: 99%
“…It also regulates trafficking of many membrane proteins implicated in trans-membrane transport, such as receptors for low-density lipoprotein and transferrin, transporters for amino acids, uric acid, glutamate, glucose, phosphate and cholesterol, and water channels, to control nutrient supply and metabolite discharge (Takata et al, 2008;Gournas et al, 2010;Tachiyama et al, 2011;Koumanov et al, 2012;Sorrentino et al, 2013;Cardona-Lopez et al, 2015;Llinares et al, 2015). It can also regulate trafficking of immune molecules, such as macrophage colony stimulating factor-1, transforming growth factor, Toll/Toll-like and T-cell receptors, and major histocompatibility complex (MHC) class II antigen, to modulate innate and adaptive immunity (Lund and Delotto, 2011;ten Broeke et al, 2013;Lou et al, 2014;Balogh et al, 2015;Wi et al, 2016). Moreover, the MVB pathway can be merged with autophagy for degradation of damaged proteins or subcellular organelles to deal with various stresses (Muller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%